The global burden of foodborne parasitic diseases: An update - Torgerson, Paul R.; Silva, N.R. de; Fèvre, Eric M.; Kasuga, F.; Rokni, M.B.; Zhou, X.N.; Sripa, B.; Gargouri, N.; Willingham, Arve Lee; Stein, C. (Elsevier, 2014)
Foodborne diseases (FBDs) are a major cause of morbidity and mortality in the human population. Accurate information on the burden of FBDs is needed to inform policy makers and allocate appropriate resources for food safety control and intervention. Consequently, in 2006 the WHO launched an initiative to estimate the global burden of FBDs in terms of Disability Adjusted Life Years (DALYs). This review gives an update of the progress on evaluating the burden of foodborne parasitic diseases that has been generated by this study. Results to date indicate that parasitic diseases that can be transmitted through food make a substantial contribution to the global burden of disease.